Fetus Cardiovasculler - Yusrawati yusrawati; Muhammad Iqbal; Reyhan Julio azwan; Bobby Indra Utama; Joserizal Serudji; Hudila rifa karmia (Universitas Andalas, 2022)
Formation of the human heart involves complex biological signals, interactions, specification of myocardial progenitorcells, and heart tube looping. To facilitate survival in the hy poxemic intrauterine environment, the fetus possessesstructural, physiological, and functional cardiovascular adaptations that are fundamentally different from the neonate. The fetal circulation is considered to anatomical and biochemical changes in the cardiovascular system. This review article describes key cardiac progenitors involved in embryonic heart development; the cellular, physiological, and anatomical changes during the transition from fetal to neonatal circulation.